Innovating Public Service Quality Assessment: A Contextual Validation of Gronroos's Model in Ethiopia - Legas, Abreham; Abagissa, Jemal (Universitas Negeri Surabaya, 2025)
In the domain of public sector service quality research, scholarly attention has traditionally placed greater emphasis on the functional dimensions of service delivery, often at the expense of adequately examining technical quality and image, two elements that play a particularly pivotal role within the governance contexts of emerging economies. This study responds to this limitation by proposing and empirically validating an innovative and context-sensitive adaptation of Grönroos’s three-dimensional service quality model. Based on a survey of 384 public service users in Ethiopia, the findings show that functional quality, technical quality, and organizational image are distinct yet interrelated factors that jointly shape citizens’ perceptions of overall service quality and satisfaction. The core innovative contribution of the study lies in the contextual validation and extension of the model, offering a more comprehensive analytical framework that expands the traditionally narrow focus on functionality to systematically include governance critical dimensions such as technical competence and institutional reputation. This innovative framework serves as a robust and reliable analytical tool for assessing public services in institutional environments characterized by low trust and limited capacity. Moreover, the study puts forward three strategically oriented managerial innovations for reform: the development of integrated training programs that simultaneously build technical expertise and citizen-oriented service skills; the explicit embedding of governance principles, including equity and transparency, into service delivery processes; and the systematic enhancement of institutional legitimacy through stronger accountability and participatory feedback mechanisms. Together, these insights provide a practical and innovative roadmap for transforming public administration and rebuilding citizen trust across diverse emerging economy contexts